Achieving carbon-rich silicon-containing ceramic anode for advanced lithium ion battery. Issue 8 (1st June 2019) - Idrees, Muhammad; Batool, Saima; Zhuang, Qiang; Kong, Jie; Seok, Ilwoo; Zhang, Jiaoxia; Liu, Hu; Murugadoss, Vignesh; Gao, Qiang; Guo, Zhanhu
Abstract: Silicon carbon (Si/C) materials are promising anode candidates for high performance lithium ion batteries (LIBs). However, serious volume expansion and solid electrolyte interface formation limited their actual capacity during lithiation and delithiation. In the present study, an innovative and low-cost synthetic approach was developed for synthesizing carbon-rich silicon-containing polymer-derived ceramics from poly(dimethylsilyene)diacetylenes (PDSDA) and its feasibility to be used as anodes was demonstrated. The attained PDCs@800 °C exhibited a high specific capacity upto 883 mAhg −1 at 400 mAg −1, with >99% coulombic efficiency (CE), and 90% capacity retention even after 500 cycles, setting a new record for PDCanode materials in LIBs. The high specific capacity was attributed to the incessant Si/C network which delivered consistent conductance and a stable solid electrolyte interphase (SEI). This study opens the door to explore and apply well-designed ceramic materials derived from tailored polymers as high performance anodes for lithium ion batteries.